A Game Theoretic Study for Distributed Multiprotocol Coexistence in ISM Band - Terzi, Ejmel; Tureli, M. S. Ufuk; Tureli, Didem Kivanc (IEEE, 2020)
Developing internet of things (IoT) applications have led to an interest in coexistence between IEEE 802.11 and IEEE 802.15.4 standards. However, existence and efficiency of steady state point for those scenarios are the critical issues because of asynchronous bandwidth and power properties of these standards. In this article, we present a power minimization game in which 802.11 links update the transmit power by selecting the optimal transmit/receive beamformer pair with the release of 802.11n standard while 802.15.4 devices only update the output power of single antenna. The regret matching learning algorithm running at 802.11n receivers achieves an equilibrium point in noncooperative fashion. The results show that the coarse correlated equilibrium exists, and the total power consumed in equilibrium is the near optimal solution.
Keywords: MIMO; coexistence; ISM band; game theory; Computer Science; Engineering